An Alkoxy‐Solubilizing Decacyclic Electron Acceptor for Efficient Ecofriendly As‐Cast Blade‐Coated Organic Solar Cells. Issue 6 (20th March 2020) - Han, Xiaona; Zhu, Jingshuai; Xiao, Yiqun; Jiang, Haotian; Zhang, Zhenzhen; Wang, Jiayu; Li, Zhen; Lin, Yuze; Lu, Xinhui; Zhan, Xiaowei
Abstract : The rapid development of organic solar cells (OSCs) based on nonfullerene acceptors has achieved significant breakthroughs in the power conversion efficiency (PCE) of spin‐coated devices. However, the spin‐coating method in a protective atmosphere seems unsuitable for the practical printing of high‐performance solar panels. In addition, the use of highly toxic solvents is also a stumbling block to the commercial application of OSCs. Thus, photoactive materials for scalable coating and ecofriendly manufacturing approaches are necessary to be developed for OSCs. Herein, a fused‐ring electron acceptor named F10IC2 bearing a decacycle core and solubilizing alkoxyl side chains is synthesized and applied in as‐cast blade‐coated OSCs by blending with polymer donor PTB7‐Th. As‐cast OSCs based on PTB7‐Th: F10IC2 blended films fabricated from chlorobenzene or chlorine‐free o ‐xylene solvents in air without any posttreatment deliver a PCE of 12.5% and 11.4%, respectively, which are among the highest values reported for as‐cast blade‐coated OSCs. Herein, a strategy of alkoxyl solubilizing to design high‐performance material systems for ecofriendly scalable OSCs is provided, which is suitable for future industrial production. Abstract : A fused‐ring electron acceptor (F10IC2) with solubilizing alkoxy side chains is designed and synthesized, and as‐cast blade‐coated organic solar cells based on PTB7‐Th: F10IC2 blended films are fabricated from chlorobenzene or chlorine‐free o ‐xylene as solvents in air without any post‐treatment deliver a PCE of 12.5% and 11.4%, respectively.